POSSIBLE ABUSE OF AUTHORITY BY STATE ADMINISTRATIVE OFFICERS IN THE DEVELOPMENT AND IMPLEMENTATION OF PUBLIC POLICIES - Mohammad Ilham Maulana; Mohammad Alauddin Alex Umein (Awang Long Law Review, 2021)
Power motivated by evil intentions is to have the inherent perfection of power, because power can do what it wants, act on behalf of and for its power on the basis of law. explained that constitutional law in maintaining the rule of law requires its implementation, otherwise power itself is determined by legal boundaries. Therefore, law and authority are not absolute in a society that regulates law in the sense that society is governed by law and no action or power is abused.